People their needs - our responsibility [soundrecording] - Conant, Ralph; American Library Association. Conference (92nd). (Los Angeles CREDR Corp, 1974)
Defines probable needs of the US population in the near future in terms of political philosophies and importance of information and education. Urges higher priorities for education and libraries among others. Outlines libraries' responsibilities in servicing the library's information needs. Challenges librarians to become active collectively in local and national politics to further their desired needs. Highlights the responsibilities of libraries in reducing ignorance and illiteracy around the world. Points out that the establishment of libraries historically proceeds the development of readers. Outlines current and future needs for boos, particularly in developing countries.
People : their needs - our responsibility / Ralph Conant (25 min.) -- Needs of people as to reading / Herman Liebaers (30 min.)
American Library Association, 92nd annual conference. Audio cassette library for professional librarians.
Keywords: Libraries and readers -- Congresses; Books and reading -- Congresses; Library science; Education